2003
DOI: 10.1046/j.1464-5491.2003.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

How do people with Type 2 diabetes perceive and respond to cardiovascular risk?

Abstract: Patients were unaware how strongly diabetes influences cardiovascular risk. Their ideas about risk were very different from those of conventional medicine, and provided individual rationales for making choices about treatment and risk-influencing behaviour. Contextual factors, such as family milieu, also influenced their behaviour. Clinicians should not assume patients share the same mental model of risk as they, and must be prepared to explore peoples' individual constructs and health beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 19 publications
3
42
1
Order By: Relevance
“…This is true in the US (Merz, Buse, Tuncer, & Twillman, 2002), and such results have been replicated in other countries (Carroll, Naylor, Marsden, & Dornan, 2003; Lai, Chie, & Lew-Ting, 2007). …”
Section: Resultsmentioning
confidence: 73%
“…This is true in the US (Merz, Buse, Tuncer, & Twillman, 2002), and such results have been replicated in other countries (Carroll, Naylor, Marsden, & Dornan, 2003; Lai, Chie, & Lew-Ting, 2007). …”
Section: Resultsmentioning
confidence: 73%
“…A study evaluating the knowledge level of stroke risk factors among primary care patients found that DM had the lowest identification rate as a risk factor. 36 Other studies also showed a considerable percentage of patients who did not recognize this condition as a risk factor. 37,38 This may lead to general underestimation of risk in our study population since a significant proportion of patients have DM.…”
Section: Discussionmentioning
confidence: 97%
“…It was found that 79 patients discharged following treatment for heart attack showed no correlation between their perceived risk of another heart attack and their TIMI scores (a measure of risk post heart attack) 65. A small study of 20 patients with diabetes showed that only 7 considered diabetes as a risk factor for CVD 66. Strecher et al67 evaluated whether smokers had a more realistic perception of their CVD risk than nonsmokers and found that although smokers were more likely to perceive themselves as at a higher risk of heart attack and stroke, they were still more likely than nonsmokers to have optimistic bias.…”
Section: Patients’ Perception Of Their Cvd Riskmentioning
confidence: 99%